Densidade de plantas no desempenho agronômico de duas cultivares de soja e fitossociologia de espécies daninhas no cerrado de Roraima - Menezes, Pedro Henrique Santos de (2017)
The arrangement of plants is a management practice that has been studied over the years and shows, in soybean, an association with the spatial distribution modification and the increase of yield per area. Phytosociological surveys in crop area are of great importance, as they provide which species are highlighted. These indices allow the knowledge of the most important weeds within the weed community, for which we must determine management alternatives or even changes in the system, in order to enable its control. The objective of this study was to evaluate the effects of different densities of soybean plants on agronomic characteristics and also to identify weeds in different management areas of soil preparation for soybean cultivation in the Cerrado of Roraima. The experiments were implemented and conducted in cerrado area, in the experimental field Água Boa of Embrapa Roraima. For the plant arrangement experiments, a randomized block design was used in a 2x4 factorial scheme, with four replications. The treatments consisted of two years of soybean cultivation, sown in four plant densities. The following agronomic characteristics were evaluated: plant height; height of the first pod insertion; stem diameter; number of node on stem; number of pods per plant; number of branches per plant; dry mass of the plant; crop index and grain yield. The data obtained from the measured variables were submitted to analysis of variance with application of the F test at 5% probability. The values referring to the means of the cultivars were compared by the Tukey test at 5% of probability and those referring to the effects of plant densities were measured by polynomial regression analysis. The weed phytosociology experiment was carried out in three different areas. For the samplings a square of welded iron was used in the ends with dimensions of 0.50 x 0.50 m. It was identified the class, family, scientific name, common name and described the type of propagation, growth habit, life cycle and dry mass (%). A descriptive analysis of the phytosociological parameters was carried out: relative density, relative frequency, relative dominance, importance value index and relative importance index. The Weed Similarity Index was calculated for the areas. The highest average yield of BRS 8381 soybeans is obtained with the population of 387,448 plants per hectare and BRS Tracajá soybean is obtained with 240,000 plants per hectare in the cerrado of Roraima. The treatments used favored the appearance of new weed species. Among the species collected in the area, the botanical families Poaceae, Cyperaceae, Fabaceae and Rubiaceae are the most representative.